2017
DOI: 10.3389/fmicb.2017.02211
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nucleic Acid Isothermal Amplification Methods for Human Clinical Microbial Infection Detection

Abstract: Battling infection is a major healthcare objective. Untreated infections can rapidly evolve toward the condition of sepsis in which the body begins to fail and resuscitation becomes critical and tenuous. Identification of infection followed by rapid antimicrobial treatment are primary goals of medical care, but precise identification of offending organisms by current methods is slow and broad spectrum empirical therapy is employed to cover most potential pathogens. Current methods for identification of bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Several LAMP-based protocols have been successfully developed and applied for the effective detection of pathogenic organism. [2224] In our study, the LAMP assay was performed for the detection of pathogenic bacteria in patients with LRTI, the bacteria amount excreted from lower respiratory tract was very little or absent, the detectable rate of both the sputum or bronchoalveolar lavage fluid samples was relatively too low to diagnose the LRTI by culture method. On the other side, the diagnostic method used in this study, which combined isothermal amplification methods and microfluidics chip, displaying high specificity and sensitivity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several LAMP-based protocols have been successfully developed and applied for the effective detection of pathogenic organism. [2224] In our study, the LAMP assay was performed for the detection of pathogenic bacteria in patients with LRTI, the bacteria amount excreted from lower respiratory tract was very little or absent, the detectable rate of both the sputum or bronchoalveolar lavage fluid samples was relatively too low to diagnose the LRTI by culture method. On the other side, the diagnostic method used in this study, which combined isothermal amplification methods and microfluidics chip, displaying high specificity and sensitivity.…”
Section: Discussionmentioning
confidence: 96%
“…[1719] The LAMP reaction employs a bacillus stearothermophilus DNA polymerase (Bst) with strand-displacement activity and a set of suitable primers that bind to 6 distinct regions on the target DNA, which makes the initial denaturation step obsolete and can be performed under isothermal conditions without costly equipment such as thermal cycler equipment. [2022] Based on these properties, the LAMP approaches have been widely used for the detection of pathogens in clinical diagnostics as a rapid, accurate and cost-effective method. [2326] Additionally, it was demonstrated that LAMP assay can be combined with microfluidic chips for improved practicability in clinical diagnostics and it can be appropriate in primary hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Isothermal amplification methods such as LAMP have been widely used in the detection of pathogens in sputum samples ( Bentaleb et al, 2016 ; Etchebarne et al, 2017 ; Wang et al, 2016 ). For tuberculosis detection, Bentaleb et al (2016) demonstrated that the LAMP assay successfully amplified target pathogen from homogenized sputum samples with 4% NaOH solution.…”
Section: Nucleic Acid Extraction From Oral and Nasal Samplesmentioning
confidence: 99%
“…In this device, the bacterial cells were trapped on the paper, and then the captured cells were directly used for in-situ HDA amplification in the tip. Similarly, Etchebarne et al (2017) demonstrated a direct LAMP assay without DNA extraction from concentrated bacterial cells in urine samples. However, low detection sensitivity was observed for the direct amplification assays without nucleic acid extraction ( Wand et al, 2018 ).…”
Section: Nucleic Acid Extraction From Urine Samplesmentioning
confidence: 99%
“…Positive reactions can be visualised by naked eye (i.e., without post-amplification steps) following the increase of sample turbidity or colour owing to the addition of fluorescent dyes (Notomi et al, 2015). Being less sensible than PCR to inhibition and not significantly influenced by non-target DNA, direct LAMP assays are currently used for point of use diagnostic in clinical and environmental settings, with good analytical performances on moderately pre-treated samples and in a range of temperature, pH and elongation times (Etchebarne et al, 2017;Samhan et al, 2017). Low amount of DNA can be amplified up to generating 10 9 copies within 1 h and producing as final amplification product a complex stem-loop DNA, with several inverted repeats of the target and cauliflower-like structures.…”
Section: Target-based Techniques For Detection and Quantification Of mentioning
confidence: 99%